2010
DOI: 10.1103/physrevd.82.043515
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the stochasticity of halos in large-scale structure surveys

Abstract: In recent work (Seljak, Hamaus and Desjacques 2009) it was found that weighting central halo galaxies by halo mass can significantly suppress their stochasticity relative to the dark matter, well below the Poisson model expectation. In this paper we extend this study with the goal of finding the optimal mass-dependent halo weighting and use $N$-body simulations to perform a general analysis of halo stochasticity and its dependence on halo mass. We investigate the stochasticity matrix, defined as $C_{ij}\equiv<… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
287
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(310 citation statements)
references
References 40 publications
22
287
1
Order By: Relevance
“…Local bias argues for a minimal level of stochasticity on large scales (Coles 1993;Scherrer & Weinberg 1998) and investigations of halo clustering suggest that halos of different masses do roughly trace the same large-scale structure (e.g, Seljak & Warren 2004;Hamaus et al 2010). Accordingly, we may expect galaxies to be roughly non-stochastic (e.g., Tegmark & Bromley 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Local bias argues for a minimal level of stochasticity on large scales (Coles 1993;Scherrer & Weinberg 1998) and investigations of halo clustering suggest that halos of different masses do roughly trace the same large-scale structure (e.g, Seljak & Warren 2004;Hamaus et al 2010). Accordingly, we may expect galaxies to be roughly non-stochastic (e.g., Tegmark & Bromley 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We are assuming Poisson noise. Simulations have shown that nonoverlapping mass ranges can exhibit off-diagonal shot-noise, and mass-dependent weighting schemes can suppress the total shotnoise contamination (Hamaus et al 2010). However, the error in estimating the cross-correlation between tracers is dominated by the individual noises in each tracer, so that our Poisson assumption is not unreasonable.…”
Section: Hi-g Cross-noisementioning
confidence: 99%
“…Bonoli & Pen (2009);Hamaus et al (2010) found that there are two to three eigenmodes in C g ij . This motives us to adopt the following fiducial model of the intrinsic galaxy clustering,…”
Section: Testing the Abs Methods Against The Fiducial Casementioning
confidence: 99%
“…Numerical simulations suggest that C g ij has only limited degrees of freedom. We only need 2 or 3 eigenmodes to describe the matrix C halo ij , the cross power spectra of halos between different halo mass bins (Bonoli & Pen 2009;Hamaus et al 2010). Namely for halos, M = 2 or 3.…”
Section: The Abs Methodsmentioning
confidence: 99%
See 1 more Smart Citation